DEVELOPMENT OF LOCAL INSTRUCTION THEORY TOPIC STATISTICS BASED ON REALISTIC MATHEMATICS EDUCATION IN PRIMARY SCHOOL - Muhammad ilham Syarif; Taufina Taufik; Ahmad Fauzan; Irdamurni . (Institut Pendidikan Tapanuli Selatan, 2019)
This study aims to develop a local instruction theory (LIT) based on realistic mathematics education (RME) that is valid, practical, and effective on the topic of Statistics in the fourth grade of elementary school. The research method used is research design type Gravemeijer & Cobb (2013). The research was conducted in three phases, namely preparing for the experiment, experimenting in the classroom, and conducting retrospective analysis. This data is collected using curriculum analysis, observation, interviews, field notes, tests, and questionnaires. The collected data was analyzed qualitatively and quantitatively. Based on the research that has been carried out, LIT is produced which is valid, practical, and effective against students' mathematical problem solving abilities. Students can find Statistics with a series of activities, namely understanding data, collecting data, presenting data, and reading data.